AGE AND GENDER SPECIFICS OF MYOCARDIAL REMODELLING IN PATIENTS ON PLANNED HEMODIALYSIS - O. V. Rtishcheva; O. F. Kalev (Российский кардиологический журнал)
This study investigated the effects of hemodialysis, age, and gender on the development of various myocardial remodelling types. In total, 399 patients were examined: 184 on planned hemodialysis, 117 with pre-dialysis chronic kidney failure (CKF), and 98 with renal disease, but no CKF. All participants underwent standard clinical, laboratory, and instrumental tests. In both genders, the prevalence of pathological types of myocardial remodelling increased from CKF-free patients to patients with pre-dialysis CKF and to hemodialysis patients. Hemodialysis was associated with eccentric left ventricular hypertrophy (LVH), as one of the most adverse remodelling types, only in young women. The effects of age on structural myocardial remodelling differed by gender. In particular, among older hemodialysis patients, compared to their younger peers, concentric LVH was more prevalent in women, while concentric remodelling was more prevalent in men.